(untitled) (Sustainability in Debate, 2014)
Although rural woman are usually considered key to sustainable development at the international level, their work in cattle-raising continues to be under-recognized by most policymakers from Uruguay. This fact has forced many young women to migrate towards urban areas, leading to the “masculinization” of Uruguayan cattle-raising. National statistics tend to ignore unpaid activities performed by rural women ”“ which they consider as “non-productive”-, as well as women’s evolving role in cattle-raising. By using semi-structured interviews and participant observation, this work analyzed: i) the organization of work of women in family farms devoted to beef and milk production Uruguay, including the role of chiefs, co-chiefs and passive observers, ii) their decision-making processes, and iii) their personal insights about cattle-raising. Five factors were identified as key to their work profiles: family relations, socio-economic status, size of the productive unit, presence of permanent employees, and formal land and/or cattle tenure.